Assessing Genomic Diversity and Productivity Signatures in Dianzhong Cattle by Whole-Genome Scanning - Zhang, Xianfu; Qu, Kaixing; Jia, Peng; Zhang, Jicai; Liu, Jianyong; Lei, Chuzhao; Huang, Bizhi (Frontiers in Genetics, 2021)
Dianzhong cattle is a classic Chinese indigenous cattle breed with historical records dating back to 200 BC. But its genomic differences have not clearly elucidated, the quest for genomic characterization will be an essential step towards understanding the genomic basis of productivity and adaptation to survival under Chinese farming systems. Here, we compared 10 Dianzhong cattle (4 newly sequenced and 6 downloaded) with 29 published genomes of three underlying ancestral populations (Chinese zebu, Indian zebu and Yanbian cattle) to characterize the genomic variations of Dianzhong cattle. Dianzhong cattle has a high nucleotide diversity (0.0034), second only to Chinese zebu. Together with analyses of linkage disequilibrium decay and runs of homozygosity, Dianzhong cattle displayed higher genomic diversity and weaker artificial selection compared with Yanbian cattle. From selective sweep analysis by four methods (Fst, π-Ratio, XP-CLR and XP-EHH), the positive selective signals were mainly manifested in candidate genes and pathways related to heat resistance, growth and development, fat deposition and male reproduction. Missense mutations were detected in candidate genes, SDS (c.944C>A, p.Ala315Glu), PDGFD (c.473A>G, p.Lys158Arg) and DDX4 (rs460251486, rs722912933 and rs517668236), which related to heat resistance, fat deposition and spermatogenesis respectively. Our findings unravel at the genome-wide level, the unique diversity of Dianzhong cattle while emphasizing the opportunities for improvement of livestock productivity in further breeding programs.